2020
DOI: 10.1371/journal.ppat.1008949
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and pathogenesis of SARS-CoV-2 infection in rhesus macaques: A nonhuman primate model of COVID-19 progression

Abstract: The COVID-19 has emerged as an epidemic, causing severe pneumonia with a high infection rate globally. To better understand the pathogenesis caused by SARS-CoV-2, we developed a rhesus macaque model to mimic natural infection via the nasal route, resulting in the SARS-CoV-2 virus shedding in the nose and stool up to 27 days. Importantly, we observed the pathological progression of marked interstitial pneumonia in the infected animals on 5–7 dpi, with virus dissemination widely occurring in the lower respirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 37 publications
4
95
0
2
Order By: Relevance
“…By Study Day 18, most clinical disease signs (including radiographic findings) had either completely resolved or were resolving, and virus in lung tissue was below the limit of detection by ISH. Prior studies have demonstrated the ability to consistently detect SARS-CoV-2 virus by immunohistochemistry of ISH in formalin-fixed tissues collected prior to Study Day 10 [ 25 27 ]. However, similar to the data described herein, assessment of tissues by these methods after Study Day 10 typically leads to negative results.…”
Section: Discussionmentioning
confidence: 99%
“…By Study Day 18, most clinical disease signs (including radiographic findings) had either completely resolved or were resolving, and virus in lung tissue was below the limit of detection by ISH. Prior studies have demonstrated the ability to consistently detect SARS-CoV-2 virus by immunohistochemistry of ISH in formalin-fixed tissues collected prior to Study Day 10 [ 25 27 ]. However, similar to the data described herein, assessment of tissues by these methods after Study Day 10 typically leads to negative results.…”
Section: Discussionmentioning
confidence: 99%
“…Before this vaccine was released for clinical study by the CFDA under No. 2020L00020, the protective efficacy of the vaccine was tested in the macaque challenge test [11] , [12] , and various toxicity studies, including an acute toxicity test, a long-term toxicity test and an allergic test, demonstrated its safety in nonhuman primates and rodents. The placebo contained only the same amount of Al(OH) 3 in buffer.…”
Section: Methodsmentioning
confidence: 99%
“…The administration of neutralizing antibodies targeting spike protein was prophylactically and therapeutically effective in NHP models [ 69 , 90 ]. NHP models have an important advantage in preclinical studies in that immune responses following SARS-CoV-2 infection recapitulate crucial aspects of COVID-19 in humans [ 91 , 92 ]. For this reason, researchers evaluating different vaccine platforms including adenovirus vectored [ 46 , 93 , 94 ], DNA [ 95 ], mRNA [ 96 ], inactivated [ 44 ], and subunit vaccines [ 97 ] have applied NHP models for assessing the immunogenicity and protective efficacy.…”
Section: Non-human Primatesmentioning
confidence: 99%